Effect of rice residues management and liming on soybean yield - Silva, José Ronaldo Coelho (Pesquisa Agropecuaria Brasileira, 1998)
The effect of rice (Oryza sativa L.) residues management and liming on soil physical and chemical properties and on soybean yield were evaluated in greenhouse on a sandy loam allic Yellow Latosol. Soil samples were collected in areas submitted to three conditions: no-tillage savanna vegetation (S), rice residues incorporation and harrowing (RI) and grazing of rice residues and harrowing (GR). Values of porosity, base saturation, pH and organic matter content were higher in C and decreased in GR while soil density decreased in the former and increased in the latter. The highest soybean yields were obtained in S and RI at the lime rating of 3 t/ha, recommended to increase base saturation to 50%.